ANALISIS KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK PADA PEMBELAJARAN FISIKA SMA MATERI FLUIDA DINAMIS DI SMA NEGERI 7 PADANG - Muhammad Rizki; Fuja Novitra; Festiyed; Hayyu Yumna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creative thinking skills are one of the 21st-century skills that are important to develop in physics learning. However, the profile of students' creative thinking ability in dynamic fluid materials still needs to be studied as a basis for improving learning. This study aims to describe the creative thinking ability of senior high school students in dynamic fluid materials. The study employed a quantitative descriptive approach involving 69 students of Grade XI at SMA Negeri 7 Padang in the 2025/2026 Academic Year, selected through a purposive sampling technique. Data were collected using an essay test based on Munandar's creative thinking indicators, which had been validated by experts, and were analyzed descriptively. The results showed that the average percentage of students' creative thinking skills was 50.63%, categorized as sufficient. The percentages for the indicators of fluency, flexibility, originality, and elaboration were 61%, 51.5%, 49.5%, and 40.5%, respectively. The findings indicate that students are more capable of generating various ideas than of developing ideas in detail, while their originality and elaboration skills still need improvement. Therefore, the results of this study can serve as a reference for teachers in designing physics learning activities that support the development of students' creative thinking skills.